2010
DOI: 10.1007/s12033-010-9273-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient DNA Extraction from Nail Clippings Using the Protease Solution from Cucumis melo

Abstract: Owing to the increasing importance of genomic information, obtaining genomic DNA easily from biological specimens has become more and more important. This article proposes an efficient method for obtaining genomic DNA from nail clippings. Nail clippings can be easily obtained, are thermostable and easy to transport, and have low infectivity. The drawback of their use, however, has been the difficulty of extracting genomic material from them. We have overcome this obstacle using the protease solution obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Amplification of 911-and 969-bp PCR products in fingernail DNA samples was unsuccessful. In the majority of fingernail samples they tested, YoshidaYamamoto and colleagues (10) were able to amplify a 286-bp fragment of the ESRX gene. In conclusion, our study and other studies have shown that toenail DNA is considerably fragmented to sizes generally <200 bp, but larger fragments are present and can be amplified in part of the samples, probably depending on the protocols used to isolate the DNA from the nails and the specific genomic regions of interest to be amplified.…”
Section: Dna Yield and Puritymentioning
confidence: 99%
“…Amplification of 911-and 969-bp PCR products in fingernail DNA samples was unsuccessful. In the majority of fingernail samples they tested, YoshidaYamamoto and colleagues (10) were able to amplify a 286-bp fragment of the ESRX gene. In conclusion, our study and other studies have shown that toenail DNA is considerably fragmented to sizes generally <200 bp, but larger fragments are present and can be amplified in part of the samples, probably depending on the protocols used to isolate the DNA from the nails and the specific genomic regions of interest to be amplified.…”
Section: Dna Yield and Puritymentioning
confidence: 99%
“…In a previous study, Li [3] evaluated 59 clostridiopeptidase and trypsin to develop an improved method 60 for recovering DNA from bone. We evaluated DNA recovery using 61 proteinase K, bromelain, and papain due to their success in a study 62 of DNA recovery from fingernail clippings; bromelain exhibited a 63 1.78-fold higher keratinolytic activity than proteinase K [4]. Both 64 bromelain and papain outperformed proteinase K [4].…”
mentioning
confidence: 99%
“…We evaluated DNA recovery using 61 proteinase K, bromelain, and papain due to their success in a study 62 of DNA recovery from fingernail clippings; bromelain exhibited a 63 1.78-fold higher keratinolytic activity than proteinase K [4]. Both 64 bromelain and papain outperformed proteinase K [4]. 65 Proteinase K (EC 3.5.21.64), a serine protease enzyme of the 66 fungus Engyodontium album (Tritirachium album Limber), has a 67 molecular weight of 18 kDa, has an optimal pH of 7.5 to 9.0 (active 68 between pH 4.0 and 12.0), and is active between 37 and 60°C 69 (<65°C) [5,6].…”
mentioning
confidence: 99%
See 2 more Smart Citations